2014
DOI: 10.1038/nm.3548
|View full text |Cite
|
Sign up to set email alerts
|

The UPF1 RNA surveillance gene is commonly mutated in pancreatic adenosquamous carcinoma

Abstract: Pancreatic adenosquamous carcinoma (ASC) is an enigmatic and aggressive tumor that has a worse prognosis and higher metastatic potential than its adenocarcinoma counterpart. Here we report that ASC tumors frequently harbor somatically acquired mutations in the UPF1 gene, which encodes the core component of the nonsense-mediated RNA decay (NMD) pathway. These tumor-specific mutations alter UPF1 RNA splicing and perturb NMD, leading to upregulated levels of NMD substrate mRNAs. UPF1 mutations are the first known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
109
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 21 publications
4
109
1
Order By: Relevance
“…We speculate that the aberrations in NMD caused by genetic alterations in the UPF1 gene lead to different disease outcomes, depending on the cell type. In premalignant glandular pancreatic cells, this may lead to reprogramming towards a squamous, more malignant state (5). In lung epithelial cells, NMD perturbation may drive a proinflammatory response, as suggested by our results herein.…”
Section: Author Contributionssupporting
confidence: 55%
“…We speculate that the aberrations in NMD caused by genetic alterations in the UPF1 gene lead to different disease outcomes, depending on the cell type. In premalignant glandular pancreatic cells, this may lead to reprogramming towards a squamous, more malignant state (5). In lung epithelial cells, NMD perturbation may drive a proinflammatory response, as suggested by our results herein.…”
Section: Author Contributionssupporting
confidence: 55%
“…The patient was then enrolled on a phase I trial involving a combination PI3K and MEK inhibitor, and experienced a clinical benefit in the form of a dramatic decrease in his pain, along with tumor response [36] . Another genetic analysis done recently looked at 23 patients with ASCP through genomic sequencing and showed a mutation of the UPF1 gene, which encodes a RNA helicase essential for the highly conserved RNA degradation pathway, nonsense-mediated RNA decay [37] . This mutation was not seen in the adjacent normal tissue of these patient samples.…”
mentioning
confidence: 99%
“…This mutation was not seen in the adjacent normal tissue of these patient samples. The pathways that UPF1 is implicated in are not all known but appear to be involved in the normal splicing of RNA, affecting such genes as p53 [37] .…”
mentioning
confidence: 99%
“…Also, UPF1 is also involved in cell proliferation and differentiation by promoting the proliferative, undifferentiation state or the decay of mRNAs encoding many other proteins that oppose the proliferative, undifferentiated cell state [15]. Another study has shown that UPF1 is down-regulated and commonly mutated in pancreatic adenosquamous carcinoma [16]. However, no studies have investigated the exact activities of UPF1 in human gastric cancer, which promotes us to explore its roles in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%